Identifikasi Potensi Erosi Dan Besar Sedimentasi Pada Das Kaiti - Bima Saputra; Mudjiatko Mudjiatko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Change of land use in the Kaiti watershed will influence to surface flow. This surface flow will increase the potential for land erosion and sediment transport capacity. This will have a major impact on the functional life of the Cipogas Lake reservoir. The USLE method is used to estimate erosion that occurs in watersheds with the help of GIS. GIS is used to predict the size of USLE parameters. The results of the analysis show that erosion occuring in the Kaiti river basin classified as heavy class (>480 Tons/Ha/Year) and the erosion potential that will enter the Kaiti reservoir is 216,273.387 tons/yr. Keyword:land erosion, USLE method, GIS, Cipogas lake reservoir